Norayu Sdn. Bhd. / Norhidayu Rosli - Rosli, Norhidayu (2020)
Norayu SDN. BHD. is a company that located in Shah Alam, Selangor that produces and supplies BeautyB which is make up line that provide essential oils in the foundation and customization of durable pod. The product provide five basic make up item that is attach to the durable pod. Several features for BeautyB have been introduced that are very useful and convenience for the most women. The target market of our company is mostly to the broad range of women from working women, housewives and also teenagers and also to the men that prefers to wear make up. This is because we believe that our product benefits our target market as our product is useful and affordable to our target market. In our business, we have several competitors in Shah Alam such NITA Cosmetics, Fame Cosmetics and Chique Cosmetics. What makes BeautyB different is we offer five basis make up item, the essential oils in the foundation and also the durable pod to protect the make up if it falls from certain heights. Our target market may choose to buy the from the ordinary make up line, but if they seek for extraordinary make up, the competition between the competitors has become lower and it gives us high advantages to our product, business and market. For the profitability, our company targets to increase the sale by 0.7% on the second year compared to the first year and 2.5% on the third year as the demand from the customers has increase and we predict to produce new products with new designs and features on the upcoming years.